WORKING WITH THE PUBLIC IS THE MAIN FEATURE OF THE DIRECTOR OF VARIETY AND PUBLIC PERFORMANCES (International Conference on Economics, Finance, Banking and Management, 2025)
This article will talk about the main specification of the director of pop and public performances and the features, problems and solutions of working his director with the public.